here we are but never were - Pobiarzyn, Monika (Tufts Archival Research Center, 2022)
here we are but never were engages with familial memory as referenced through material translation. Hand-crocheted cotton is saturated with porcelain slip and fired in a kiln, a process that burns away the fiber and leaves behind only its memory in clay- an idea of what once was. The quotidian form of the tablecloth becomes an artifact of futile labor; it is made as fragile as the relationships it alludes to, yet remains a precious object that must be approached with care.; here we are but never were attempts to memorialize. It is driven both by nostalgia and hope(less)(ful) speculation, a yearning for a unity that cannot exist and perhaps never did.